A Mixed-Methods Investigation of Medical Follow-Up in Long-Term Childhood Cancer Survivors: What Are the Reasons for Non-Attendance? - Ernst, Mareike; Brähler, Elmar; Faber, Jörg; Wild, Philipp S.; Merzenich, Hiltrud; Beutel, Manfred E. (Frontiers in Psychology, 2022)
As long-term childhood cancer survivors (CCS) are at risk for late effects, ongoing medical care is crucial to detect and treat physical illnesses as early as possible. However, previous research from around the world has shown that many adult survivors did not participate in long-term medical follow-up. This study aimed to provide insight into German survivors’ care situation, with a particular focus on barriers to follow-up care. We investigated a sample of adult CCS (N = 633) (age M = 34.92; SD = 5.70 years) drawn from the German Childhood Cancer Registry’s oldest cohort (> 25 years after diagnosis). Our analyses included data from a standardized medical examination, a self-report questionnaire, and in-depth interviews with a subsample (n = 43). Half of the participants (n = 314, 49.6%) reported participating in some kind of medical follow-up. In a logistic regression analysis, attendance of medical follow-up care was associated with higher age. Reasons for non-attendance were assigned to four categories: lack of information about medical follow-up and/or its purpose (n = 178), termination by the health care provider (n = 53), structural barriers (n = 21), and emotional-motivational aspects (n = 17). The interviews contributed to a better understanding of how these reported barriers played out in the care of individual survivors. Further, they revealed that some survivors currently in medical follow-up had had periods without follow-up care in the past - which were also in many cases related to a lack of information, both on the part of health care providers and CCS themselves. The results indicated that a large proportion of long-term CCS do not receive the recommended follow-up care. Further, there is a great need for more information regarding the aims of long-term medical follow-up and available offers. This is an important prerequisite for CCS to make informed decisions.